Perspectivas historiográficas en torno al caudillismo argentino del siglo XIX - Camareno, Hernán (2000)
The author describes, classifies, and analyzes various approaches to the themes of “Caudillismo” in nineteenth-century Argentina, and concludes with a reflection  on the most recent contributions in this area, which have brought about a profound revision of concepts and ideas.